2013
DOI: 10.7762/cnr.2013.2.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Risk at Admission on the Length of Hospital Stay and Mortality in Gastrointestinal Cancer Patients

Abstract: This retrospective study was conducted to determine whether increased length of hospital stay (LOS) and mortality are associated with nutritional risk upon hospital admission in gastrointestinal cancer patients, using a computerized screening tool developed by a university hospital. We included adult gastrointestinal cancer patients whose hospital stays ranged from 24 hours to 90 days. The sample included 4,345 patients. The average age of the patients was 60.5 ± 11.4 years and 2,959 (68.1%) were males. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The MCA map for neoplastic patients evidenced that the variables death and LOHS ≥7 days were associated with many indicators of nutritional risk according to the NRS, malnutrition according to the SGA, underweight according to BMI, depletion of lean and fat masses according to body composition parameters, and recent weight loss. These findings have been described by other studies using another type of analysis (1,2,22,23,24) . The present study has found that nutritional status-related variables are associated with routine clinical outcomes during hospital stay.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The MCA map for neoplastic patients evidenced that the variables death and LOHS ≥7 days were associated with many indicators of nutritional risk according to the NRS, malnutrition according to the SGA, underweight according to BMI, depletion of lean and fat masses according to body composition parameters, and recent weight loss. These findings have been described by other studies using another type of analysis (1,2,22,23,24) . The present study has found that nutritional status-related variables are associated with routine clinical outcomes during hospital stay.…”
Section: Discussionsupporting
confidence: 65%
“…For many years, many studies have reported undesirable outcomes that may occur during the hospital stay of patients diagnosed with malnutrition or even at some nutritional risk (28,31) . These findings have been observed in patients with neoplasms, digestive tract diseases, and other clinical situations (22,24,31) .…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations